Strategies to reduce stigma related to visible chronic skin diseases: a systematic review. (5th August 2019) - Topp, J.; Andrees, V.; Weinberger, N. A.; Schäfer, I.; Sommer, R.; Mrowietz, U.; Luck‐Sikorski, C.; Augustin, M.
Abstract: Many patients with a visible chronic skin disease experience discrimination and stigmatization. This results in psychosocial impairments in addition to the burden of disease and emphasizes the urgency to implement effective stigma‐reduction strategies. To synthesize what is known globally about effective interventions to reduce stigma associated with visible chronic skin diseases, a systematic review was conducted. Four electronic databases were searched until May 2018. Studies evaluating interventions to reduce stigmatization in patients with visible chronic skin diseases and applying at least one stigma‐related outcome measure were included. Data were extracted on study design, country, study population, outcome measures and main findings. Results were subsequently synthesized in a narrative review. Critical Appraisal Skills Programme tools were used to assess study quality. Nineteen studies were included in the review. Study design was very heterogeneous and study quality rather poor. Thirteen studies addresses patients with leprosy in low‐ and middle‐income countries, and one study each targeted patients with onychomycosis, leg ulcer, facial disfigurement, atopic dermatitis, vitiligo and alopecia. Evaluated interventions were mainly multi‐faceted incorporating more than one type of intervention. While 10 studies focused on the reduction in self‐stigma and 4 on the reduction in public stigma, another 5 studies aimed at reducing both. The present review revealed a lack of high‐quality studies on effective approaches to reduce stigmatization of patients with visible chronic skin diseases. Development and evaluation of intervention formats to adequately address stigma is essential to promote patients' health and well‐being.